Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/met6120303
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Possible Chalcopyrite Dissolution Mechanism in Sulfuric Acidic Aqueous Solution

Abstract: Abstract:The dissolution routes of chalcopyrite in acidic sulfate aqueous solution have been discussed by thermodynamic calculation under different aqueous species concentrations, such as Cu 2+ , Fe 2+ and H 2 S. The results show that for both oxidative dissolution and non-oxidative dissolution of chalcopyrite, the dissolution process undergoes several intermediate steps before completely decomposing to Cu 2+ , Fe 2+ and elemental sulfur, in which bornite and covellite are the most likely intermediates. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Table II displays the speciation results for the tailings samples obtained using phreeqc simulation software and were accurately predicted within a 10% error threshold: As seen from Table II, a reduction in the formation of calcium salt species (CaSO 4 ) along with an increase in calcium ion (Ca 2+ ) occurs over the course of the leaching period (12 hours), evident from the pH evolution behavior (Fig. 2) as higher concentrations of Ca 2+ free hydrated ionic species compete with hydrogen ion to stabilize solution pH [46]. The speciation data for Cu species also agree with the observed recovery behavior (Fig.…”
Section: Speciation Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Table II displays the speciation results for the tailings samples obtained using phreeqc simulation software and were accurately predicted within a 10% error threshold: As seen from Table II, a reduction in the formation of calcium salt species (CaSO 4 ) along with an increase in calcium ion (Ca 2+ ) occurs over the course of the leaching period (12 hours), evident from the pH evolution behavior (Fig. 2) as higher concentrations of Ca 2+ free hydrated ionic species compete with hydrogen ion to stabilize solution pH [46]. The speciation data for Cu species also agree with the observed recovery behavior (Fig.…”
Section: Speciation Resultsmentioning
confidence: 81%
“…Fe displays similar behavior to that of Cu indicating that during acid attack of hematite (the main constituent of Fe in the carbonatite tails solutions), Fe is more likely to form ferrous iron (Fe 2+ ). From previous studies it was observed that Fe is preferentially released in solution [46] before Cu as Fe 2+ ions compete with Cu 2+ ions; competition of Cu with Fe could reduce the concentration of soluble species in solution which contributes to the observed extraction behavior.…”
Section: Resultsmentioning
confidence: 97%
“…The most abundant type of copper mineral is chalcopyrite [1][2][3][4][5]. Chalcopyrite has traditionally been treated by conventional pyrometallurgical techniques [6], which consist of flotation, smelting and refining, and electrorefining [7].…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies it was found that CuSO 4 does not promote leaching in a sulphate system Error! Reference source not found.. Iron might also be released into the solution prior to copper which might also explain the low Cu 2+ concentration [30]. This will explain the reduction in the dissolution rate from hour one to twelve from 18.8% to 1.02% dissolution rate of copper in the ferric sulphate media as the dominant Cu species is CuSO 4 which gradually increases from hours one to twelve with an overall decrease in the Cu 2+ concentration as well as an increase observed in the concentration of free hydrated iron species Fe 2+ .…”
Section: Speciation Resultsmentioning
confidence: 99%